The Use of N-Smsin (Nurse -Short Message Service Information) Telenursing Application Technology on Compliance With Treatment and Care of Tuberculosis Patients in Preventing Transmission and the Occurrence of Multi Drug Resistant Tuberculosis - Indra Rahmad,; Muhtar, Muhtar; Maruni Wiwin Diarti,; Julhana,; Ahmad, (International Journal of Scientific Research and Management (IJSRM), 2025)
Tuberculosis is a chronic, infectious disease caused by the bacterium Mycobacterium tuberculosis and remains a global health problem, including in Indonesia. Worldwide, TB is one of the 10 leading causes of death. Poor adherence to treatment is a major obstacle to efficient TB control. Innovative strategies are needed to improve access and adherence to treatment, one of which is the use of the Telenursing N-SMSIn (Nurse-Short Message Service Information) application. The purpose of this study was to determine the effectiveness of the Telenursing N-SMSIn (Nurse-Short Message Service Information) application on adherence to treatment and care for tuberculosis patients, preventing transmission and the occurrence of multidrug-resistant tuberculosis. The research method used a quasi-experimental pretest-posttest with a control group design. The sampling technique used accidental sampling, with a sample of 168 respondents with pulmonary TB in the Woha Community Health Center working area in 2025. The research instrument used the 8-item Morisky Medication Scale. The analysis used the Wilcoxon test and obtained a p-value of 0.001 < 0.05. Therefore, it can be concluded that the implementation of the N-SMSIn telenursing application technology significantly impacts adherence to treatment and care in tuberculosis patients, preventing transmission and the occurrence of multidrug-resistant tuberculosis in the Woha Community Health Center Work Area, Bima Regency.